O Conceito de qualidade nas orientações dos organismos internacionais e a política de avaliação externa - Azambuja, Nathália Ribeiro de Faria (2021)
This master's research is part of the State, Policies and Management in Education line of the Graduate Program in Education at the Faculty of Education of the Federal University of Uberlândia. The problem that guided the search was: How do the perspectives around the concept of quality promoted by International Organizations influence educational policies in the period from 1990 to 2020, especially in terms of evaluation? The general objective was to understand how the debate and centrality around the concept of education quality was configured and how this discussion influenced the construction of the external evaluation policy. The specific objectives were defined as follows: To analyze the influence of neoliberalism on the internationalization of educational policies and the role of International Organizations in this context; Understand the concepts that permeate the concept of educational quality, especially the conception present in the external evaluation policy; To apprehend the concept of education quality present in the guidelines of the International Organizations, from 1990 to 2020, and its relationship with the external evaluation policy. The study, a qualitative approach, was developed through bibliographical and documentary research. For the construction, interpretation of data and understanding of the research object, we used content analysis, seeking support in theoretical frameworks such as Bardin (2009) and Oliveira (2003), among others. In order to support the discussion and analysis of the documents raised, we draw on Afonso (2005), Chirinéa (2010), Dourado and Oliveira (2009), Freitas (2002, 2004, 2005, 2007, 2009, 2010, 2011, 2012 , 2014, 2018), Gentili (1997), Gusmão (2010), Laval (2019), Shiroma and Evangelista (2006) etc. educational policies. Through quality, they are undertakings and actions that seek an equitable and quality education for all. In this sense, we observe that external evaluation policies are defined systematically and constantly in all documents here, evidencing a strong association between educational quality and external evaluation, including evaluation systems as instruments for monitoring and controlling results, for management, productivity and resources. Thus, we find that the documents of the International Organizations, in this work, support the main conceptions about educational quality and influence the educational policies of countries, including Brazil. We conclude that the role of International Organizations has been fundamental in propagating the neoliberal logic, standardizing, controlling and seeking to universalize educational training. Thus, quality education is defended in the documents as one that contributes to the formation of flexible, competent, competent subjects who effectively respond to the demands of economic development.